2013
DOI: 10.1074/jbc.m113.455915
|View full text |Cite
|
Sign up to set email alerts
|

Human IL10 Gene Repression by Rev-erbα Ameliorates Mycobacterium tuberculosis Clearance

Abstract: Background: Transcriptional modulation of IL10, a cytokine that blocks phagolysosome maturation, is not well understood. Results: This study demonstrates human IL10 gene repression by direct binding of Rev-erb␣ on Rev-DR2 in the proximal promoter. Conclusion: Rev-erb␣ binds to IL10 proximal promoter, represses expression, and impedes Mycobacterium tuberculosis in human macrophages. Significance: This study provides rationale to target Rev-erb␣ as a therapeutic intervention that might support host defense in tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 51 publications
(59 reference statements)
1
55
0
Order By: Relevance
“…Our recent work along with other reports has shown that PPARg and TR4 provoke the anti-inflammatory and pro-M. tuberculosis properties of macrophages (28,32,34). In addition, different groups have also reported other nuclear receptors such as vitamin D receptors, Rev-erba, and LXRa anti-infectives functions against M. tuberculosis (27,28,(61)(62)(63)(64)(65).…”
Section: Discussionmentioning
confidence: 99%
“…Our recent work along with other reports has shown that PPARg and TR4 provoke the anti-inflammatory and pro-M. tuberculosis properties of macrophages (28,32,34). In addition, different groups have also reported other nuclear receptors such as vitamin D receptors, Rev-erba, and LXRa anti-infectives functions against M. tuberculosis (27,28,(61)(62)(63)(64)(65).…”
Section: Discussionmentioning
confidence: 99%
“…Conclusion-Many of the key studies supporting a role for heme in recruiting NCoR1 to Rev-erb NRs are based on experiments with the ␣-isoform (16,21,34,86,109), which is more extensively studied, likely because of its discovery prior to Reverb␤ and its unique context in the genome being transcribed on the opposite strand of the gene coding for THR␣ on chromosome 17 (2, 9), whereas Rev-erb␤ is encoded on chromosome 3. Because the DBD and LBD of the two receptors share a high level of homology and nearly identical heme binding properties (9,36), it has been assumed that the mechanism of heme regulation would be the same for both isoforms.…”
Section: An Unknown Factor Present In Cell Extracts Mediates the Effementioning
confidence: 99%
“…[5][6][7][8][9] Our recent report establishes its role in ameliorating Mycobacterium tuberculosis clearance by direct repression of the human IL10 gene. 10 Recent reports, including our study on the role of NR1D1 in infection and inflammation, suggest that NR1D1 behaves as an equilibrist whereby it finetunes the regulatory pathways in order to maintain the equilibrium in cellular processes. [10][11][12] Many proteins are involved in the expulsion of bacterium from the host.…”
Section: Introductionmentioning
confidence: 99%
“…10 Recent reports, including our study on the role of NR1D1 in infection and inflammation, suggest that NR1D1 behaves as an equilibrist whereby it finetunes the regulatory pathways in order to maintain the equilibrium in cellular processes. [10][11][12] Many proteins are involved in the expulsion of bacterium from the host. These include CLEC7A/dectin-1, TLRs (toll-like receptors), dendritic cell-specific CD209/DC-SIGN, soluble Ctype lectins such as SFTPA (surfactant protein A), SFTPD and MBL (mannose-binding lectin), VDR (vitamin D [1,25-dihydroxyvitamin D3] receptor), and NR1H/LXR.…”
Section: Introductionmentioning
confidence: 99%